Will I Stay or Will I Go? Explaining Repatriation by Self-Initiated Expatriates - Tharenou, Phyllis; Caulfield, Natasha (Academy of Management Journal, 2010)
Offering an integrated framework, we sought to explain why and how professionals who self-initiate expatriation repatriate. We measured host country “pull” and “push,” home country pull, “shocks,” and the intention to repatriate of 546 Australians and, a year later, their home country job search during the preceding year and whether they had repatriated. We found that host country pull (weak embeddedness), home country pull, and shocks explained their intention to repatriate and that shocks also played a key role in explaining job search and repatriation. The mediation of host country embeddedness, home country pull, and shocks by intention, and of intention by job search, explained how repatriation occurred.